Endothelin-1 and endothelin B receptor expression in pancreatic adenocarcinoma. Issue 4 (8th January 2015) - Cook, N; Brais, R; Qian, W; Hak, C Chan Wah; Corrie, P G
Abstract : Background: Endothelin-1 (ET-1) acting through endothelin A and B receptors (ETAR and ETBR) has been implicated in the development of cancer. The endothelin axis has not previously been characterised in human pancreatic adenocarcinoma (PAC). Methods: Expression of ET-1, ETAR, ETBR, vascular endothelial growth factor and microvessel density (MVD) was determined by immunohistochemistry in 45 surgically resected human PACs and 15 non-cancer human pancreas samples. Results: PAC had the highest staining intensity for ET-1 and ETBR: 38% PAC samples scored 2+ or more compared with 7% non-cancer sample in ET-1; 58% PAC samples scored 2+ compared with 0% non-cancer samples in ETBR. MVD was significantly lower in PAC compared with non-cancer tissue (p<0.0001). Conclusions: PAC was characterised by greater expression of ET-1 and ETBR compared with normal pancreas.